Authorship: practices and experiences in the Faculty of Health Sciences of the University of the Free State - G. Joubert (South African Family Practice)
Background: The allocation of authorship of papers can lead to controversy. In medical journals, papers tend to be multi-authored and the contribution of each author is not always apparent. The International Committee for Medical Journal Editors provides clear guidelines regarding rights to authorship, and these guidelines are used by some journals. We wished to propose guidelines for the Faculty of Health Sciences of the University of the Free State (UFS) and, in order to do so, first determined the practices and experiences regarding authorship in the Faculty.